Prevalence and Molecular Characterization of Fluoroquinolone-Resistant Escherichia coli in Healthy Children - Zhao, Qiang; Shen, Yueyun; Chen, Gang; Luo, Yanping; Cui, Shenghui; Tian, Yaping (Frontiers in Cellular and Infection Microbiology, 2021)
Faecal E. coli can act as reservoirs for resistance genes. Here, we analyzed prevalence of drug resistance in faecal E. coli isolated from healthy children at a kindergarten in Beijing, China, then used whole genome sequencing to characterize fluoroquinolone-non-susceptible strains. Our results revealed high resistance to ampicillin (54.0%), trimethoprim/sulphurmethoxazole (47.5%) and tetracycline (58.9%) among 576 faecal E. coli isolates, 49.2% of which exhibited multidrug resistance. A total of 113 E. coli isolates were not susceptible to ciprofloxacin, with four sequence types, namely ST1193 (25.7%), ST773 (13.3%), ST648 (8.8%) and ST131 (7.1%) found to be the most prevalent (54.9%). With regards to resistance to quinolones, we detected chromosomal mutations in gyrA, parC, and parE in 111 (98.2%), 105 (92.9%), and 67 (61.1%) isolates, respectively. blaCTX-M (37.2%) was the major ESBL gene, whereas blaCTX-M-14 (12.4%) and blaCTX-M-27 (11.5%) were the most frequent subtypes. A total of 90 (79.6%) ExPEC and 65 (57.5%) UPEC isolates were classified. Overall, these findings revealed clonal spread of certain prevalent STs, namely ST1193, ST773, ST648 and ST131 E. coli isolates in healthy children within a single kindergarten in Beijing, China, affirming the seriousness of the multidrug resistance problem and potential pathogenicity of E. coli isolates in healthy children. Therefore, there is an urgent need for increased surveillance to enhance control of this problem.